Terapia assistida por animais como recurso terapêutico no atendimento a crianças enlutadas - Castro, Ligiane Pigatto de (2011)
Given the need to broaden the range of resources to equip the psychologist with intervention techniques in caring for bereaved children, this research aims to understand the implications of the inclusion of a co-psychotherapist dog in the psychodiagnostic process of this population. To this end, subsidies of the Attachment Theory, the literature on mourning and Animal Assisted Therapy were used. This is a research of qualitative and interpretive nature, based on a case study involving a child mourning the loss of his father after a period of one year. A semistructured interview with the mother, playful interviews with the child and a feedback interview with the mother were used as research tools. During the psychodiagnostic process a co-therapist dog was present in the therapeutic setting, and for the data analysis, a content analysis was performed. It was observed that the therapy duo, psychologist and co-therapist dog, assumes the attachment figure to the child. The co-therapist dog acted as a bond formation facilitator, a mediator of the relationship with the therapist and a catalyst for the psychodiagnostic assessment process. The presence of the co-therapist dog also worked as a motivational feature for the child in the psychodiagnostic process, since the animal's presence encouraged the child to return. Although the purpose of this research has been the development of a psychodiagnosis, its results can be extended to the care of bereaved children in the form of a bereavement psychotherapy, to the extent that the animal acts as a resource for coping in the context the child s loss